Sustainable production and consumption of paper products - Lim, Wei Hian (2023)
The overall aim of this research was to understand on the balance between what is best for the society while preserving profitability for bathroom tissues manufacturers through marketing in Singapore and to compare how it aligns with consumer. To address these objectives, an empirical research on green value was given to consumers to analyse 1) Their knowledge versus the perception of the paper producing and processing industry. 2) The main challenges to sustainability in the paper processing industry and consumer values on sustainability. 3) Consumer price sensitivity and demographics on how they make their purchasing decision. In total there were 76 respondents and empirical results will be discussed in relation to the reviewed literature. The key findings are that: 1) Respondents have weak understanding of the recycling guidelines in Singapore 2) Respondent demonstrated that they have general knowledges to the main challenges to sustainability on the bathroom tissue paper processing industry. 3) There is a significant gap in respondents ‘awareness on products that are environmentally certified. 4) Environmental values have somehow limited influence over purchasing habits. 5) Marketers need to do more to promote more ethical consumer behaviour. It is suggested that government, companies and NGO policies needed to be strengthened for green consumers to close the attitude-behaviour gap.